(untitled) (The Research of Medical Science Review, 2025)
This study aims to investigate the effects of estrogen levels on the mental health of unmarried and married females in Hyderabad City, Sindh, Pakistan. The primary focus is on the correlation between estrogen levels and indicators of depression, anxiety, and stress among these demographic groups. The study included 150 participants, with a mean age of 32.5 years. Estrogen levels were found to vary significantly between married and unmarried females, with married females exhibiting more stable levels. Higher estrogen levels were generally associated with lower scores on the DASS-21, indicating reduced symptoms of depression, anxiety, and stress. Married females, particularly those in menopausal transition, reported higher stability in mental health indicators compared to their unmarried counterparts. Socioeconomic status and age also moderated the relationship between estrogen levels and mental health, with higher socioeconomic status linked to better mental health outcomes. Correlation analysis showed correlation coefficient for the anxiety is 0.38; indicating moderate positive correlation between depression and anxiety scores and for stress correlation coefficient is 0.44 also moderate positive between and depression and stress scores. The correlation coefficient of -0.095 indicates a very weak negative correlation between anxiety scores estrogen levels while correlation coefficient of 0.08 between stress scores and estrogen levels indicates a very weak positive correlation. The strongest correlations in this analysis exist between the different components of the DASS scores (depression, anxiety, and stress), which is expected as they measure related aspects of psychological distress. Correlation analysis showed correlation coefficient for the anxiety is 0.38; indicating moderate positive correlation between depression and anxiety scores and for stress correlation coefficient is 0.44 also moderate positive between and depression and stress scores. The correlation coefficient of -0.095 indicates a very weak negative correlation between anxiety scores estrogen levels while correlation coefficient of 0.08 between stress scores and estrogen levels indicates a very weak positive correlation. The strongest correlations in this analysis exist between the different components of the DASS scores (depression, anxiety, and stress), which is expected as they measure related aspects of psychological distress.